2020
DOI: 10.1002/pep2.24145
|View full text |Cite
|
Sign up to set email alerts
|

Bent into shape: Folded peptides to mimic protein structure and modulate protein function

Abstract: Protein secondary and tertiary structure mimics have served as model systems to probe biophysical parameters that guide protein folding and as attractive reagents to modulate protein interactions. Here, we review contemporary methods to reproduce loop, helix, sheet, and coiled‐coil conformations in short peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 248 publications
(242 reference statements)
0
44
0
Order By: Relevance
“…However, as well as previously reported EPO-derived peptides, our peptides, including ML1-h3, still are in a native form, and this study leaves enough room for the development of more advanced EPO-derived peptides. So far, chemical modifications have been established to improve the stability and bioavailability of peptide drugs with advanced synthetic chemistry [ 97 , 98 ]. Acetylation at N-terminal, cyclization of N- to C-terminal, incorporation of N-methylated or unnatural amino acid, replacement to amide bond mimetics such as thioamides, peptoids, and β-amino acids, PEGylation, and lipidation have been used for peptide drug development.…”
Section: Discussionmentioning
confidence: 99%
“…However, as well as previously reported EPO-derived peptides, our peptides, including ML1-h3, still are in a native form, and this study leaves enough room for the development of more advanced EPO-derived peptides. So far, chemical modifications have been established to improve the stability and bioavailability of peptide drugs with advanced synthetic chemistry [ 97 , 98 ]. Acetylation at N-terminal, cyclization of N- to C-terminal, incorporation of N-methylated or unnatural amino acid, replacement to amide bond mimetics such as thioamides, peptoids, and β-amino acids, PEGylation, and lipidation have been used for peptide drug development.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to demonstrate the utility of BRC8-2 in a functional cellular assay for disruption of radiation-induced RAD51 foci formation. Strategies to further stabilize this -hairpin may involve the use of tryptophantryptophan cross-strand pairs 40 or even artificial crosslinks such as triazole 41 , to achieve an additional enhancement of binding through a reduction in conformational heterogeneity prior to complex formation (as well as improving resistance to proteolytic degradation). Our work revealed that the linker between the FxxA module and LFDE module is also likely to play a role in determining the affinity of the peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Even though β‐sheets occur frequently in PPIs, [4] the corresponding mimetics have been less explored as PPI inhibitors [5] . In general, most β‐sheet mimetics are based on β‐hairpin peptides which comprise two antiparallel β‐strands connected by a turn [5b, 6] . The β‐hairpin structure can be stabilized by backbone modifications within the β‐strands, β‐sheet‐inducing turn mimetics and by hairpin macrocyclization [5–7] .…”
Section: Introductionmentioning
confidence: 99%